Penerapan Contextual Teaching and Learning Dalam Perspektif Ontologi Dan Epistemologi Filsafat Pendidikan Matematika - Riky Irawan; Anies Fuady (FKIP Universitas Mataram, 2026)
Mathematics learning is often perceived as an abstract activity detached from students’ real-life contexts, which results in low meaningfulness and conceptual understanding. The Contextual Teaching and Learning approach offers an alternative by connecting mathematical concepts to students’ real experiences; however, studies examining this approach from the perspective of the philosophy of mathematics education remain limited. This research aims to analyze the implementation of Contextual Teaching and Learning from the ontological and epistemological perspectives of the philosophy of mathematics education. This study employs a qualitative method in the form of library research, combined with descriptive and philosophical analysis of CTL from ontological and epistemological viewpoints within the philosophy of mathematics education. The findings indicate that, ontologically, CTL views mathematics as meaningful and contextual knowledge whose existence is understood through students’ learning experiences. Epistemologically, CTL is grounded in constructivism, positioning students as active subjects who construct mathematical knowledge through experience, interaction, and reflection. The synthesis of these two perspectives affirms that CTL is not merely a teaching approach, but rather a philosophically coherent paradigm of mathematics education. The conclusion of this study demonstrates that the implementation of CTL has a strong philosophical foundation and is relevant for fostering meaningful, contextual mathematics learning oriented toward students’ conceptual understanding.